Effect of canagliflozin on the pharmacokinetics of glyburide, metformin, and simvastatin in healthy participants. Issue 3 (27th October 2014) - Devineni, Damayanthi; Manitpisitkul, Prasarn; Murphy, Joseph; Skee, Donna; Wajs, Ewa; Mamidi, Rao N. V. S.; Tian, Hong; Vandebosch, An; Wang, Shean‐Sheng; Verhaeghe, Tom; Stieltjes, Hans; Usiskin, Keith
Abstract Drug–drug interactions between canagliflozin, a sodium glucose co‐transporter 2 inhibitor, and glyburide, metformin, and simvastatin were evaluated in three phase‐1 studies in healthy participants. In these open‐label, fixed sequence studies, participants received: Study 1‐glyburide 1.25 mg/day (Day 1), canagliflozin 200 mg/day (Days 4–8), canagliflozin with glyburide (Day 9); Study 2‐metformin 2, 000 mg/day (Day 1), canagliflozin 300 mg/day (Days 4–7), metformin with canagliflozin (Day 8); Study 3‐simvastatin 40 mg/day (Day 1), canagliflozin 300 mg/day (Days 2–6), simvastatin with canagliflozin (Day 7). Pharmacokinetic parameters were assessed at prespecified intervals. Co‐administration of canagliflozin and glyburide did not affect the overall exposure (maximum plasma concentration [Cmax] and area under the plasma concentration–time curve [AUC]) of glyburide and its metabolites (4‐trans‐hydroxy‐glyburide and 3‐cis‐hydroxy‐glyburide). Canagliflozin did not affect the peak concentration of metformin; however, AUC increased by 20%. Though Cmax and AUC were slightly increased for simvastatin (9% and 12%) and simvastatin acid (26% and 18%) following coadministration with canagliflozin, compared with simvastatin administration alone; however, no effect on active 3‐hydroxy‐3‐methyl‐glutaryl‐CoA (HMG‐CoA) reductase inhibitory activity was observed. There were no serious adverse events or hypoglycemic episodes. No drug–drug interactions were observed between canagliflozin and glyburide, metformin, or simvastatin. All treatments were well‐tolerated in healthy participants.